2007
DOI: 10.1007/s00167-007-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the graft angles for the anterior cruciate ligament reconstruction with transtibial technique using postoperative magnetic resonance imaging in comparative study

Abstract: The aims of this study were to quantify the angle and placement of an anterior cruciate ligament (ACL) grafted with a single incision ACL reconstruction technique using postoperative magnetic resonance imaging (MRI), and to compare the results with those with a native ACL. Between February 1996 and May 2004, 96 consecutive patients, who had undergone postoperative MRI of the knee followed by an arthroscopically assisted ACL reconstruction with either a hamstring tendon or bone-patellar tendon-bone (BTB) autogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 41 publications
7
75
0
5
Order By: Relevance
“…Additionally, the orientation angles of the ACL reported in this study (Figs. 5 and 6) are in general agreement with the literature in which cadaveric and MRI-based studies have reported traditional transtibial ACL reconstruction to orient the graft at 65-718 in the sagittal plane and 73-788 in the coronal plane 19,20,40 compared to native ACL angles of 51-598 in the sagittal plane and 66-708 in the coronal plane. 19,20,40 It is important to note that the purpose of this study was not to determine whether it is possible to place the single-bundle ACL graft in the center of the native footprints using the transtibial surgical technique.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, the orientation angles of the ACL reported in this study (Figs. 5 and 6) are in general agreement with the literature in which cadaveric and MRI-based studies have reported traditional transtibial ACL reconstruction to orient the graft at 65-718 in the sagittal plane and 73-788 in the coronal plane 19,20,40 compared to native ACL angles of 51-598 in the sagittal plane and 66-708 in the coronal plane. 19,20,40 It is important to note that the purpose of this study was not to determine whether it is possible to place the single-bundle ACL graft in the center of the native footprints using the transtibial surgical technique.…”
Section: Discussionsupporting
confidence: 88%
“…5 and 6) are in general agreement with the literature in which cadaveric and MRI-based studies have reported traditional transtibial ACL reconstruction to orient the graft at 65-718 in the sagittal plane and 73-788 in the coronal plane 19,20,40 compared to native ACL angles of 51-598 in the sagittal plane and 66-708 in the coronal plane. 19,20,40 It is important to note that the purpose of this study was not to determine whether it is possible to place the single-bundle ACL graft in the center of the native footprints using the transtibial surgical technique. The purpose of the study was to extend a recently developed measurement technique to characterize the 3D, in vivo differences in the side-to-side ACL footprint position in healthy subjects and then to apply this technique to retrospectively evaluate patient-specific graft position in both the tibia and femur of a cohort of patients with unilateral ACL reconstruction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Achieving an anatomic footprint is considered critical to achieving tibiofemoral stability after an ACL reconstruction [1,3,10,11,30,38,43], yet there is currently little agreement on the ideal footprint placement of a singlebundle ACL reconstruction. McConkey et al [30] showed that when 12 surgeons reviewed the femoral and tibial tunnels in 72 cadaveric knees, there was poor agreement (\5%) on what was considered the ideal tunnel placement, although 88% of the femoral tunnels and 78% of the tibial tunnels were created within the study criteria [4].…”
Section: Discussionmentioning
confidence: 99%
“…This type of reconstruction (i.e., more vertical positioning of the graft) may result in a functional graft that will not impinge on the roof, but it will not reproduce the actual anatomy of the native anterior cruciate ligament. Two recent magnetic resonance imaging studies have shown that contemporary anterior cruciate ligament grafts are more vertical than the native anterior cruciate ligament 38,39 . Therefore, we propose that a reconstruction of the anterior cruciate ligament should be performed with consideration of the three-dimensional positioning of the ligament within the knee.…”
Section: Kinematicsmentioning
confidence: 99%